Quantitative analysis of polysorbates 20 and 40 by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. (31st October 2013) - Zhang, Qi; Meng, Yang; Yang, Huaxin; Xiao, Xinyue; Li, Xiaodong
Abstract : RATIONALE: Polysorbates are nonionic surfactants that consist primarily of fatty acid esters of polyethoxy sorbitan. This study proved that polysorbates can be quantitatively analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Using MALDI‐TOF MS, relative intensity and concentration ratios were correlated, and extensive research was conducted to understand the influencing factors. METHODS: Polysorbate 20 and 40 were mixed in the desired ratios and irradiated with a N2 laser. MALDI‐TOF mass spectra were recorded in positive ion mode to test the linearity. All commercial polysorbates were analyzed to determine the relative concentration of the components using the same method. RESULTS: The relative peak intensity ratio as a function of the relative concentration ratio was analyzed, and a reasonably good linearity ( R 2 = 0.987 for polysorbate 20) was obtained. This study illustrates the process of converting the analyte signal response into the concentration, supporting the notion that quantitative MALDI‐TOF MS can be used to analyze polymers. MALDI‐TOF MS analysis of commercial polysorbate formulations revealed a complex mixture of oligomers that was related to the fatty acid composition. CONCLUSIONS: Polysorbates 20 and 40 were characterized, and the simultaneous quantitative analysis of polysorbate 20 was reported. This method requires no tedious sample pretreatment. Therefore, it is a promising method for the rapid simultaneous quantitation of polysorbates 20 and 40. Copyright © 2013 John Wiley & Sons, Ltd.